Mitochondrial Fusion Potentially Regulates a Metabolic Change in Tibetan Chicken Embryonic Brain During Hypoxia - Tang, Qiguo; Ding, Cui; Xu, Qinqin; Bai, Ying; Xu, Qiao; Wang, Kejun; Fang, Meiying (Frontiers in Cell and Developmental Biology, 2021)
The Tibetan chickens (Gallus gallus; TBCs) are an indigenous breed found in the Qinghai-Tibet Plateau that are well-adapted to a hypoxic environment. As of now, energy metabolism of the TBCs embryonic brain has been little examined. This study investigated changes in energy metabolism in TBCs during hypoxia, and compared energy metabolism in TBCs and Dwarf Laying Chickens (DLCs), a lowland chicken breed, to explore underlying mechanisms of hypoxia adaptation. We found TBCs exhibited decreased oxygen consumption rates (OCR) and ATP levels as well as an increased extracellular acidification rate (ECAR) during hypoxia. Nevertheless, OCR/ECAR ratios indicated aerobic metabolism still dominated under hypoxia. Most important, our results revealed significant differences in TBCs brain cellular metabolism compared to DLCs under hypoxia. Compared to DLCs, TBCs had higher OCR and TCA cycle activities during hypoxia. Also, TBCs had more mitochondrial content, increased mitochondrial aspect ratio and MFN1, MFN2, and OPA1 proteins which have previously been reported to control mitochondrial fusion were expressed at higher levels in TBCs compared to DLCs, suggesting that TBCs may regulate energy metabolism by increasing the level of mitochondrial fusion. In summary, TBCs can reduce aerobic metabolism and increase glycolysis to enable adaptation to hypoxia. Regulation of mitochondrial fusion via MFN1, MFN2, and OPA1 potentially enhances the ability of TBCs to survive on the Qinghai-Tibet Plateau.